An overview: Matrix tablets as sustained release. - Nagendrakumar, D; Keshavshetti, G G; Shardor, A G (Recent Research in Science and Technology, 2014)
Oral route is the most preferred route for administration of drugs. Tablets are the most popular oral formulation available in the market and preferred by the patients and physician alike. In long-term therapy for the treatment of chronic disease conditions, conventional formulations are required to be administered multiple doses and therefore have several disadvantages. The primary benefit of a sustained release dosage form compared to a conventional dosage form, is the uniform drug plasma concentration and therefore uniform therapeutic effect. Matrix system are favored because of their simplicity, patient compliance etc, than traditional drug delivery which have many drawbacks like repeated administration, fluctuation in blood concentration level etc. Introduction of Matrix tablet as Sustained release has given a new break through for novel drug delivery system (NDDS) in the field of Pharmaceutical technology. Matrix systems are widely used for the purpose of sustained release. It is the release system which prolongs and controlls the release of drug that is dissolved or dispersed. In fact, a matrix is defined as a well-mixed composite of one or more drugs with gelling agent i.e. hydrophilic polymers. By the sustained release method therapeutically effective concentration can be achieved in the systemic circulation over an extended period of time, thus achieving better compliance of patients. Numerous sustained release oral dosage forms such as membrane controlled system, matrices with water soluble/insoluble polymers or waxes and osmotic systems have been developed, intense research has been recently focused on the designed of sustained release systems for poorly water soluble drugs.